Electrophysiological, haemodynamic, and mitochondrial alterations induced by levobupivacaine during myocardial ischemia in a pig model: protection by lipid emulsions?. (3rd August 2015) - Mamou, Zahida; Descotes, Jacques; Chevalier, Philippe; Bui‐Xuan, Bernard; Romestaing, Caroline; Timour, Quadiri
Abstract: Accidental intravascular or high‐dose injection of local anesthetics (LA) can result in serious, potentially life‐threatening complications. Indeed, adequate supportive measures and the administration of lipid emulsions are required in such complications. The study's objectives were threefold: (i) evaluate the myocardial toxicity of levobupivacaine when administered intravenously; (ii) investigate levobupivacaine toxicity on cardiomyocytes mitochondrial functions and cellular structure; (iii) assess the protective effects of a lipid emulsion in the presence or absence of myocardial ischemia. Domestic pigs randomized into two groups of 24 animals each, with either preserved coronary circulation or experimental myocardial ischemia. Six animals from each group received either: (i) single IV injection of saline, (ii) lipid emulsion (Intralipid ® ), (iii) levobupivacaine, (iv) combination levobupivacaine‐Intralipid ® . Serially measured endpoints included: heart rate, duration of the monophasic action potentials (dMAP), mean arterial pressure, and peak of the time derivative of left ventricular pressure (LV dP/dtmax ). In addition, the following cardiomyocytes mitochondrial functions were measured: reactive oxygen species (ROS) production, oxidative phosphorylation, and calcium retention capacity (CRC) as well as the consequences of ROS production on lipids, proteins, and DNA. IV injection of levobupivacaine induced sinus bradycardia and reduced dMAP and LV dP/dtmax . At the mitochondrial level, oxygen consumption and CRC were decreased. In contrast, ROS production was increased leading to enhanced lipid peroxidation and structural alterations of proteins and DNA. Myocardial ischemia was associated with global worsening of all changes. Intralipid ® quickly improved haemodynamics. However, beneficial effects of Intralipid ® were less clear after myocardial ischemia.